Towards an architecture of simplification? Victor Horta’s lectures on American architecture in the 1920s (Bulletin KNOB, 2023)
The Belgian architect Victor Horta (1861-1947) spent most of the First World War in the United States. Over the course of three years, from December 1915 to January 1919, he explored how the American skyscrapers, standardized dwellings and ingenious urban planning might serve as a model for a modern, post-war Belgium.Yet Horta’s memoirs had very little to say about his discussion of American architecture or any influence his travels might have had on his post-war work. This article consequently breaks new ground in examining the various talks on the subject that Horta gave in the 1920s. Horta’s lectures actually provide a good picture of how he started to see American architecture as a model for the future. In American architectural practice, serial production, standardization and economies of scale facilitated a simplification of the design – a solution Horta also proposed for war-torn Belgium.By way of illustration, the article describes the affinity between Horta’s more classical formal language of the 1920s, as in his 1925 pavilion for the Exposition international des Arts décoratifs et industriels modernes, and the architecture of the United States. It also shows that Horta was an important proponent of American architecture in Belgium, and also played a pioneering role in the introduction of some of its defining features, such as high-rise construction.